Identification and Quantification of Major Faba Bean Seed Proteins - Warsame, Ahmed O; Michael, Nicholas; O'Sullivan, Donal M; Tosi, Paola (Journal of agricultural and food chemistry, 2020)
Faba bean ( ) holds great importance for human and animal nutrition for its high protein content. However, better understanding of its seed protein composition is required in order to develop cultivars that meet market demands for plant proteins with specific quality attributes. In this study, we screened 35 diverse genotypes by employing the one-dimensional sodium dodecyl sulfate-polyacrylamide gel electrophoresis (1D SDS-PAGE) method, and 35 major protein bands obtained from three genotypes with contrasting seed protein profiles were further analyzed by mass spectrometry (MS). Twenty-five of these protein bands (MW range: ∼ 9-107 kDa) had significant (p ≤ 0.05) matches to polypeptides in protein databases. MS analysis showed that most of the analyzed protein bands contained more than one protein type and, in total, over 100 proteins were identified. These included major seed storage proteins such as legumin, vicilin, and convicilin, as well as other protein classes like lipoxygenase, heat shock proteins, sucrose-binding proteins, albumin, and defensin. Furthermore, seed protein extracts were separated by size-exclusion high-performance liquid chromatography (SE-HPLC), and percentages of the major protein classes were determined. On average, legumin and vicilin/convicilin accounted for 50 and 27% of the total protein extract, respectively. However, the proportions of these proteins varied considerably among genotypes, with the ratio of legumin:vicilin/convicilin ranging from 1:1 to 1:3. In addition, there was a significant (p < 0.01) negative correlation between the contents of these major fractions (r = -0.83). This study significantly extends the number of identified seed proteins and reveals new qualitative and quantitative variation in seed protein composition, filling a significant gap in the literature. Moreover, the germplasm and screening methods presented here are expected to contribute in selecting varieties with improved protein content and quality.